The Effect of PGPR Bacteria on Botrytis Cinerea Fungus in Tomato Plants (Growth and Production Standards) - صالح منتجب; ياسر حماد; رامز الشامي (Latakia University Journal -Biological Sciences Series, 2025)
The research aimed to study the effect of a mixture of bacterial species that stimulate plant growth and reduce the effect of the fungus Botrytis Ceneria and its symptoms on tomato plants grown in bags in a greenhouse in 2023 AD, and to measure some vegetative growth indicators related to the number of leaves on the plant and the fresh weight of the vegetative and root systems. The results showed an increase in the growth of tomato plants, and a reduction in the effect of the pathogenic fungus Botrytis Ceneria on the number of leaves, fresh and dry weight of shoot and root systems, number of flowers, and root length, compared to the healthy control and those infected with the fungus not treated with bacteria. Treatment with the mixture of bacterial species used in the experiment was significantly superior in all studied indicators, whether infected or not infected with the pathogenic fungus Botrytis Ceneria in tomato plants. Therefore, it is possible to use bacterial inoculation with mixed bacterial species by adding them to plant seedlings to improve their growth, productivity, and resistance to plant diseases.